2013
DOI: 10.1177/0956462413482423
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with erectile dysfunction in a cohort of HIV-infected patients

Abstract: To determine the prevalence of erectile dysfunction and its associated factors we conducted an observational study on a consecutive cohort of asymptomatic HIV-positive men. All the patients completed a questionnaire to evaluate erectile dysfunction based on the International Index of Erectile Function, a validated survey for the diagnosis of anxiety and depression (self-administered HAD), and a questionnaire about cardiovascular risk factors. Epidemiological, clinical, and analytical data were collected. In al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 26 publications
(42 reference statements)
5
37
0
7
Order By: Relevance
“…Although anxiety and guilt were not included in our evaluation, they have been previously assessed [ 35 ]. We also acknowledge that as the aim of this study was to relate metabolic and clinical variables with ED in patients with HIV, some other confounding variables were not included in our evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Although anxiety and guilt were not included in our evaluation, they have been previously assessed [ 35 ]. We also acknowledge that as the aim of this study was to relate metabolic and clinical variables with ED in patients with HIV, some other confounding variables were not included in our evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The side effects experienced from taking necessary ART to prevent HIV progression is potentially a factor influencing the SRHR experiences of YPLWH ( 20 ). Evidence suggests that possible side effects of ART (and perhaps HIV infection itself) may negatively impact on sexual functioning – including decreased libido and erectile dysfunction – further affecting the SRHR of YPLWH ( 32 ).…”
Section: Treatment Adherence and Side Effectsmentioning
confidence: 99%
“…More recently, the 2011 US National Health and Wellness Survey showed that 24.6% of men aged 40 years and older had ED [10]. However, the reported prevalence of ED has appeared to be higher among HIV-infected men, ranging 25%–74% in various study populations [57, 1114]. Using more stringent methodological criteria including adequate sample sizes and a validated questionnaire for ED assessment, a 2014 review found an ED prevalence of 50%–60% in HIV-infected men [15].…”
Section: Introductionmentioning
confidence: 99%